2008
DOI: 10.2169/internalmedicine.47.1114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors on Cavitary and Nodular Bronchiectatic Types in Pulmonary Mycobacterium avium Complex Disease

Abstract: Background and Objective Pulmonary Mycobacterium avium complex (MAC) disease is the most common pulmonary non-tuberculous mycobacteriosis (NTM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 7 publications
2
58
1
Order By: Relevance
“…The BMI of patients with PNTM disease was lower than that of age-, sex-and race-matched controls or uninfected healthy controls in previous studies (4,23,24). Ikegame et al reported that BMI at baseline is associated with disease spread in terms of the number of affected lung segments in PNTM disease (6).…”
Section: Discussionmentioning
confidence: 87%
“…The BMI of patients with PNTM disease was lower than that of age-, sex-and race-matched controls or uninfected healthy controls in previous studies (4,23,24). Ikegame et al reported that BMI at baseline is associated with disease spread in terms of the number of affected lung segments in PNTM disease (6).…”
Section: Discussionmentioning
confidence: 87%
“…This rate was previously reported to be 39.9% (109 of 273 MAC patients) and 20.0% (6 of 30 MAC patients) in two Japanese studies (23,24). The mechanisms of lung cavity formation under conditions of mycobacterial infection are not clear, even in cases involving M. tuberculosis.…”
Section: Discussionmentioning
confidence: 86%
“…In a study by the US National Institutes of Health, the mean BMI of the pulmonary NTM disease patients was lower than that of the age-, sex-and ethnicity-matched control subjects (BMI 21.1 vs. 28.2; p<0.001) (28). In a Japanese study, the BMI values of the patients with newly diagnosed MAC disease of the cavitary and nodular bronchiectasis type were 17.9±2.7 and 18.4±2.6 kg/m 2 , respectively (23). BMI has also been reported to be a marker of deterioration in patients with NTM disease (29).…”
Section: Discussionmentioning
confidence: 98%
“…MAC-PD is predominantly observed in postmenopausal, non-smoking, Caucasian females (Griffith et al, 2007). In Japan, among 273 newly diagnosed MAC-PD cases between 1996 and 2002, 70.3% were female with a mean age of 63.2 years (Okumura et al, 2008). The HRCT findings of MAC-PD also exhibit all three forms of lung disease, as described for NTM-PD, namely cavitary disease, fibronodular bronchiectasis, and HP (Cappelluti et al, 2003;Embil et al, 1997;Glassroth, 2008;Kahana et al, 1997).…”
Section: Mycobacterium Avium Complexmentioning
confidence: 91%
“…Typical HRCT findings are often observed in the right middle lobe or lingual, which are anatomically predisposed to impaired clearance of secretions, a condition referred to as "Lady Windermere syndrome" (Reich & Johnson, 1992). Fibronodular bronchiectasis is most common in elderly women without preexisting pulmonary conditions or histories of tobacco abuse, but who often have anatomic abnormalities of the chest Daley & Griffith, 2002;Dhillon & Watanakunakorn, 2000;Field & Cowie, 2006;Iseman et al, 1991;Jarzembowski & Young, 2008;Okumura et al, 2008;Prince et al, 1989;Taiwo & Glassroth, 2010). The major symptom www.intechopen.com of fibronodular bronchiectasis is a persistent cough, and the disease can result in severe lung damage, although many patients experience a less aggressive, chronic course (Prince et al, 1989;Taiwo & Glassroth, 2010).…”
Section: Fibronodular Bronchiectasismentioning
confidence: 99%